PEMBERDAYAAN EKONOMI KELOMPOK NELAYAN TANGKAP DALAM UPAYA OPTIMALISASI TANGKAPAN IKAN PRODUK PEKASAM KEMASAN DI DESA PANGKALAN SERAI - Evi Marlina; Hasmalina Nasution; Isranbidin Isranbidin (Jurnal Pengabdian UntukMu NegeRI, 2018)
Pangkalan Serai village, one of the villages in the Kampar Kiri Hulu sub-district, is a kampar river basin that is still isolated and a part of its residents are fishermen. Catchesfishermen have generally been sold fresh, overlaid (diang on bamboo beds) for fish supplies, ormaking it into pakasam. Pakasam is a kind of side dish that is processed by fermentation methodfrom fish with special spices which are inserted into small jars or closed jars for about 10 daysand after that period it can be cooked like fried or fried. Servicer conducts community partnershipprograms in this village with guidance of two groups of fishermen, namely the group of fishermencaught in the hamlet of Muara Biwan and the hamlet of Telaga Beras. With this service activityit is expected that this fishermen group can overcome problems in household products such as fishermen not paying attention to hygienic aspects and product quality standards that are suitable for consumption. So that in the end the pekasam they produce has high economic value and istraded to increase income and family welfare.